Escola de tempo integral: avanços e desafios na experiência da Escola Monteiro Lobato - Oliveira, Gleize Ramos de (2020)
The present study integrates the research line Identities, Traditions and Territorialities of the Master's Degree Program in History and aimed to analyze the process of implementation of the full-time school Escola Municipal de Educação Integral Monteiro Lobato, located in Jardim Tiradentes in Aparecida de Goiânia, a neighborhood marked by struggles of residents demanding housing, education and infrastructure. The object of study is the social representations of the residents of the neighborhood about the full-time school EMEI Monteiro Lobato. In Brazil, the full-time school project gained popularity due to the proposal of a teaching modality, capable of rescuing poor children from school exclusion, violence and crime, through the ideas of Anísio Teixeira, who aimed to expand school time with proposed activities for intellectual, social and economic development. In this sense, we sought to reflect about the conception and implementation of the Full-Time school based on the following question: What social representations experienced in the implementation of the Monteiro Lobato Municipal School of Integral Education in Aparecida de Goiânia? Therefore, in order to better understand the theme, the research makes a historical path on public policies for the implementation of full-time schools. As parameters, we approached the Law of Directives and Bases of Education (LDB), n. 9394/96, the Brazilian Federal Constitution of 1988, the National Plan of Education (PNE), 2001- 2010.Together, we analyzed the social representations on the processes of creation of the neighborhood in face of the struggles of families in a state of social vulnerability